2017
DOI: 10.3390/biology6010012
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Chromosome Segregation Errors in Mitosis and Meiosis

Abstract: Mistakes during cell division frequently generate changes in chromosome content, producing aneuploid or polyploid progeny cells. Polyploid cells may then undergo abnormal division to generate aneuploid cells. Chromosome segregation errors may also involve fragments of whole chromosomes. A major consequence of segregation defects is change in the relative dosage of products from genes located on the missegregated chromosomes. Abnormal expression of transcriptional regulators can also impact genes on the properl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 271 publications
(315 reference statements)
2
122
1
3
Order By: Relevance
“…These observations introduce the possibility that chromosome segregation errors associated with exposure to PDGF-AA may underlie the malignant transformation of stem-like cells in which p53 or its pathway has been compromised. Indeed, segregation errors can induce mitotic arrest (27), DNA breaks (28) and apoptosis (27) and lead to gains and losses of whole chromosomes (29), features that have been documented in our system. Intriguingly, the areas of recurrent losses in our model harbor GBM-associated tumour suppressor genes.…”
Section: Discussionsupporting
confidence: 54%
“…These observations introduce the possibility that chromosome segregation errors associated with exposure to PDGF-AA may underlie the malignant transformation of stem-like cells in which p53 or its pathway has been compromised. Indeed, segregation errors can induce mitotic arrest (27), DNA breaks (28) and apoptosis (27) and lead to gains and losses of whole chromosomes (29), features that have been documented in our system. Intriguingly, the areas of recurrent losses in our model harbor GBM-associated tumour suppressor genes.…”
Section: Discussionsupporting
confidence: 54%
“…To better understand the behaviour and characteristics of the chromosomes that give rise to laggards at anaphase, we analysed 10 MII oocytes that contained 15 laggards at anaphase (Fig and Movie EV3). The lagging chromatids did not delay anaphase II onset (Fig EV5A) and did not give rise to micronuclei, the latter in contrast to what have been observed in mitotic cells . Centromere tracking revealed that the 15 lagging chromatids observed at anaphase II originated from 13 laggard‐producing chromosomes.…”
Section: Resultsmentioning
confidence: 76%
“…Aneuploidy derived from mitotic slippage caused genomic instability, since it showed an abnormal number of chromosomes [76,78,79], and subsequent cell death or senescence in a process known as mitotic catastrophe [65,74,80]. In addition, cell death induced by electric fields was caspase dependent, but the first triggers of the caspase-dependent apoptosis were not known [65].…”
Section: Discussionmentioning
confidence: 99%